STRATEGI LEMBAGA PENDIDIKAN ISLAM DALAM MENGHADAPI REVOLUSI INDUSTRI 4.0 - jakfar, jakfar (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2020)
Abstract: This study aims to determine the strategy of Islamic educational institutions in facing the industrial revolution 4.0. From the results of several studies indicate that Islamic educational institutions are a place for the implementation of education with a variety of facilities, regulations, and responsible for education imbued with the spirit of teachings and good values ​​with the intention to embody the teachings of goodness. Positive impacts, namely Increased Efficiency and Productivity, Lower Costs, Better Risk Management, Faster Identification and Problem Solving. Negative impacts are susceptible to cyber attacks, inexpensive human resources investment, technological impact on the environment Impact on human resources The strategy of the first Islamic educational institution was to change the educational system in the institution. At least from two education groups (integrative and fully digital), there will be two fundamental changes in reconstructing education. The second strategy is to prepare the profession in the era of RI 4.0 in schools / madrasas. We know that the link and match of Indonesia's education with the industry has been very weak long ago. When disruptive work in this era changes, then there is a new opportunity for the world of education to immediately adapt the work of this era. The third strategy is to reconstruct the curriculum with the three main literacy approach in RI 4.0. Calistung, which was the hallmark of the previous era, must be reconstructed as soon as possible so that education is not left behind. There are several sub strategies in implementing the curriculum reconstruction. Keywords: Strategy, Islamic educational institutions, industrial revolution 4.0